Combined intra- and extracapsular stabilization for CCL rupture in a toy-breed dog: a case report - Park, Sung Su; Han, Ho Jae (Frontiers in Veterinary Science, 2025)
Cranial cruciate ligament (CrCL) rupture is a frequent orthopedic condition leading to hindlimb dysfunction in dogs. While tibial plateau leveling osteotomy (TPLO) has become the predominant surgical choice in large breeds, its use in toy-breed dogs remains controversial due to anatomical constraints and implant limitations. This case report presents a 10-year-old, 2.0 kg Maltese with CrCL rupture and underlying cardiac disease, for whom osteotomy was contraindicated. A hybrid stabilization technique was performed, combining intra-articular suture placement with extracapsular anchoring via bone tunnels, intentionally avoiding use of the lateral fabella. The procedure resulted in rapid postoperative limb function recovery and no observed complications. This outcome highlights the potential clinical value of non-osteotomy-based stabilization in ultra-small dogs, particularly in cases where traditional methods pose excessive risk. Continued case accumulation and long-term monitoring are necessary to further validate the safety and efficacy of this approach.